Evidence of a multiple insecticide resistance in the malaria vector Anopheles funestus in South West Nigeria - Djouaka, R.F.; Atoyebi, S.M.; Tchigossou, G.; Riveron, J.; Irving, H.; Akoton, R.; Kusimo, M.O.; Bakare, A.A.; Wondji, C.S. (Springer, 2016)
Background Knowing the extent and spread of insecticide resistance in malaria vectors is vital to successfully manage insecticide resistance in Africa. This information in the main malaria vector, Anopheles funestus sensu stricto, is completely lacking in the most populous country in Africa, Nigeria. This study reports the insecticide susceptibility status and the molecular basis of resistance of An. funestus as well as its involvement in malaria transmission in Akaka-Remo, a farm settlement village in southwest Nigeria. Results Plasmodium infection analysis using TaqMan protocol coupled with a nested PCR revealed an infection rate of 8% in An. funestus s.s. from Akaka-Remo. WHO susceptibility tests showed this species has developed multiple resistance to insecticides in the study area. Anopheles funestus s.s. population in Akaka-Remo is highly resistant to organochlorines: dieldrin (8%) and DDT (10%). Resistance was also observed against pyrethroids: permethrin (68%) and deltamethrin (87%), and the carbamate bendiocarb (84%). Mortality rate with DDT slightly increased (from 10 to 30%, n = 45) after PBO pre-exposure indicating that cytochrome P450s play little role in DDT resistance while high mortalities were recorded after PBO pre-exposure with permethrin (from 68 to 100%, n = 70) and dieldrin (from 8 to 100%, n = 48) suggesting the implication of P450s in the observed permethrin and dieldrin resistance. High frequencies of resistant allele, 119F in F0 (77%) and F1 (80% in resistant and 72% in susceptible) populations with an odd ratio of 1.56 (P = 0.1859) show that L119F-GSTe2 mutation is almost fixed in the population. Genotyping of the A296S-RDL mutation in both F0 and F1 samples shows an association with dieldrin resistance with an odd ratio of 81 (P < 0.0001) (allelic frequency (R) = 76% for F0; for F1, 90 and 10% were observed in resistant and susceptible populations, respectively) as this mutation is not yet fixed in the population. Conclusion The study reports multiple insecticide resistance in An. funestus from Akaka Remo. It is, therefore, necessary to pay more attention to this major malaria vector for effective malaria control in Nigeria.